Caracterización de la basura presente en las riberas del Rio Zamora de la ciudad de Loja como una herramienta para plantear una propuesta educativa ambiental. - Ortiz Piedra, Katherine Gabriela (2019)
The present investigation was carried out with the objective of being able to show the contamination that exists in the banks of the Zamora River, as a result of the bad disposition of the trash that is thrown disproportionately, which is within one of the most important global problems that manifest the evident and inadequate management of garbage and the lack of culture of a population, which is not yet aware of the negative impacts it is causing to the resources that are so vital for our subsistence. It is necessary to propose an environmental education program aimed at raising awareness of the population on the pollution of the banks of the Zamora River in our city, the execution and development of this research was carried out with the establishment of 5 sampling points (PM), each (200m), in order to cover the entire central stretch of the Zamora River to its junction with the Jipiro River, where transects were installed every 10m on both sides of the riverbanks at the (5PM), and to the collection of garbage and its classification (cardboard, plastic bags, bottles, paper, glass, others), to later be weighed and estimate the amount of garbage in the entire study area and execute the respective analysis and interpretation. The analysis carried out indicates that the banks of the Zamora River are contaminated by the presence of rubbish, especially with the organic type and debris, belonging to the other category within the investigation, which during the sampling days exceeded in large quantity the other categories In addition, surveys were applied to support this problem, taking into account the most relevant questions, it was stated that there is a lack of information associated with working in environmental education programs that could help contribute to the conservation and improvement of the landscape environment of the riverbanks. of the Zamora river. Thus, this research addresses all this problem of the presence of garbage on the banks of the Zamora River and focuses on the structuring of an environmental education program aimed at the training and mutual work of an entire population with the sole purpose of generating a positive change for the good of all. With the tools and strategies of organization, communication and diffusion of the different activities proposed within the educational program, it is expected to achieve the awareness of all the citizens in general that contribute to preserve and restore the landscape environment of the banks of the Zamora River.